Odpowiedzi

  • Użytkownik Zadane
2009-12-13T19:58:28+01:00
Pierwsze to wzór skróconego mnożenia
1)x²-5
2) (2y-√3)(y+1)=2y²+2y-√3y-√3
3)(a+√2)(a-√3)=a²-√3a+√2a-√6
4)(2√2+k)(√2-k)=4-2√2k-√2k-k²=4-3√2k-k²
2009-12-13T20:03:59+01:00
(x+√5)(x-√5)= x² - √5x + √5x - √25= x² - 2√5x -5
(2y-√3)(y+1)= 2y² + 2y - √3y - √3
(a+√2)(a-√3)= a² + √2a - √2a - √6 = a² - √6
(2√2+k)(√2-k)= 2√4 - 2√2k + √2k - k² = 4 - 3√2 - k²

powinno być dobrze ale nie jestem pewna:)
Najlepsza Odpowiedź!
2009-12-13T20:27:46+01:00
1) (x+√5)(x-√5)=x²-5
2)(2y-√3)(y+1)=2y²+2y-√3y-√3
3)(a+√2)(a-√3)=a²+√2a-√3a-√6
4)(2√2+k)(√2-k)=4-2√2k-k²+√2k